Teaching Practicum of An English Teacher Education Program in Vietnam : From Expectations to Reality - Vo Thi Kim Anh; Vincent Pang; Lee, Kean Wah (2018)
Teaching practicum is very essential in the process of learning how to teach, so it should be paid great attention by not only teacher education program designers but also implementators. The paper reports a study on the efficiency of teaching practicum which has been conducted at Public University (pseudonym) in Vietnam. The research employed qualitative approach, and semi-structured interviews were used as the instrument for the data collection. Findings reveal that the implementation of the teaching practicum did not provide student teachers with sufficient chances to develop their teaching skill efficiently. Inappropriate method of implementing the teaching practicum, loose cooperation between the university and high schools, and insufficient support are major issues that caused the teaching practicum to be ineffective. Peer mentoring and a more suitable method of implementing the internship are recommended solutions to improve the effectiveness of the teaching practicum in the English Teacher Education Program at Public University in particular and other English teacher education programs in Vietnam in general.